MENGKRITISI MAKNA HUKUM RIBA BUNGA BANK - Sarono, Agus (Faculty of Humanities, Diponegoro University, 2015)
Bank interest is considered usury. One is to be scrutinized if the bank interest as usury, because usury is often mentioned in the texts is characterized oppress and torment the community. As with the conventional bank interest, how many small and medium enterprises which helped because Free Master in conventional banks. Problems found in the writing of this paper is; Why people ignore the MUI fatwa on usury interest as knife analysis; Unger critical legal theory, theory of responsiveness Nonet Sezlnick, the theory of legal culture Lawrence M Friedman progressive Satjipto Rahardjo and Usul Fiqh used to find alternative meanings of texts relating to usury From search and review of the problems concluded that after the birth of four Imam Muslim schools stuck in the mindset of the four Imams Madzhab and afraid to ijtihad. Therefore, the Muslims thought of usury is not far from what has been inferred by the four Imam mazdhab. Finally Islamic law really can not answer the development of society. Bank interest is equated with usury which both born differ in the time span, the different communities of the background, a different effect. Therefore interest rates clearly differ from usury and should not be equated with riba. That is why people ignore the MUI fatwa in business transactions. Should the scholars 'move from positivistic Jurisprudence to understanding Sociological Jurisprudence positivistic Jurisprudence.Oleh Hence the scholars can use the legal pluralisme approach in defining legal meaning.